The Neoliberal Urbanization in São Paulo, Brazil: the case of Agusta Park - Levy, Dan; Liguori, Carla (International Planning History Society Proceedings, 2016)
The purpose of this article is to understand the consequences of accelerated neoliberal urbanization in the city of São Paulo by analyzing the Augusta Park and it’s environs. The study is justified because this city has been pursuing neoliberal practices that generate social and urban fragmentation. The current neoliberal scenario transforms the urban space and restructures the city, it creates marginalized and segregated urban environments, and replaces public spaces with private amenities. The research question is the following: Does Augusta Park represent a kind of resistance to accelerated neoliberal urbanization in São Paulo? To support this research, we use a qualitative methodology in order to demonstrate the urban destruction that threatens this area, the object of this study. First, we contextualize the Augusta Park as a public space with twenty four thousand square metres, located on Augusta Street, in the downtown area of São Paulo, representing a significant green area, a scarce amenity in this region. Then we demonstrate that in recent years, due to the increasing valuation of real estate in the downtown area, the region has become a strong target for the property market who intend to suppress the Park to make way for modern and luxurious housing. This fact has generated a large mobilization of the park’s users, locals and others, who demand that this area be preserved and handed over to the population in the form of a public space in all of its integrity. The case remains a legal process in the courts due to the influence of real estate capital on the Government. The research aims to reveal the historical and urban importance of the Park for the region and the impact of the developers activities in the urban environment. Historically the above issues have been justified by man’s domination of his environment. So, it is inevitable to analyse the instruments for environmental protection, especially National Urban Development Policy in Brazil. In conclusion we believe that the urban landscape of the city of São Paulo is changing quickly and intensely, causing profound changes to the city’s structure. The accelerated neoliberal urbanization process contributes significantly to this scenario with the main actors being the property and financial markets. Despite neoliberal practices producing devastating effects on the local way of life, promoting the disintegration of history as well as the memory of the city and decaying urban spaces definitively, Augusta Park reveals itself as a potential resistance to this neoliberal influence.